1998
DOI: 10.1016/s0014-5793(98)01359-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional heterodimeric amino acid transporters lacking cysteine residues involved in disulfide bond

Abstract: The protein mediating system L amino acid transport, AmAT-L, is a disulfide-linked heterodimer of a permease-related light chain (AmAT-L-lc) and the type II glycoprotein 4F2hc/ CD98. The Schistosoma mansoni protein SPRM1 also heterodimerizes with h4F2hc, inducing amino acid transport with different specificity. In this study, we show that the disulfide bond is formed by heavy chain C109 with a Cys residue located in the second putative extracellular loop of the multi-transmembrane domain light chain (C164 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 17 publications
5
89
0
1
Order By: Relevance
“…1). Early studies reported that 4F2hc cysteines are not essential for transport activity (16,18). The expression of xCT together with 4F2hc without cysteines (Cysless 4F2hc) did not severely affect transport function (Fig.…”
Section: The 4f2hc-xct Heterodimer Is Inactivated By Mercurialmentioning
confidence: 88%
“…1). Early studies reported that 4F2hc cysteines are not essential for transport activity (16,18). The expression of xCT together with 4F2hc without cysteines (Cysless 4F2hc) did not severely affect transport function (Fig.…”
Section: The 4f2hc-xct Heterodimer Is Inactivated By Mercurialmentioning
confidence: 88%
“…To examine the role of CD98 heavy-light chain association on its interactions with integrins, we first investigated the effect of mutation of these cysteines (Cys 109 and Cys 330 ). The C109S (C1) mutation alone, or in combination with the C330S (Cless) mutation, is reported to reduce the amino acid transport activity of CD98 (7,25,26). However, the capacity of CD98hc to complement dominant suppression was not impaired by mutation of both or either cysteines (Fig.…”
Section: Cd98 Heavy Light Chain Association Is Not Required For the Imentioning
confidence: 99%
“…CD98hc has two extracellular cysteines, one of which (Cys 109 ) is involved in covalent association of the heavy and light chains (25). To examine the role of CD98 heavy-light chain association on its interactions with integrins, we first investigated the effect of mutation of these cysteines (Cys 109 and Cys 330 ).…”
Section: Cd98 Heavy Light Chain Association Is Not Required For the Imentioning
confidence: 99%
“…In agreement with the previous LSHAT sequences, 12 putative transmembrane domains with both cytoplasmatic N-and C-terminal segments are predicted (HMMTOP version 1.1 algorithm [26]). The cysteine residue, which is conserved in all LSHAT sequences and participates in the disulfide bridge with the corresponding heavy subunit (27), corresponds to residue 154 for oLAT-2 and residue 151 for oy ϩ LAT-1.…”
Section: Opossum Lat-2 and Y ϩ Lat-1 Proteins Belong To The Lshat Familymentioning
confidence: 99%